Measurements of electron-phonon coupling factor and interfacial thermal resistance of metallic nano-films using a transient thermoreflectance technique - 王海东 马维刚 过增元 张兴 王玮 (Chinese physics B, 2011)
Using a transient thermoreflectance （TTR） technique, several Au films with different thicknesses on glass and SiC substrates are measured for thermal characterization of metMlic nano-films, including the electron phonon coupling factor G, interfazial thermal resistance R, and thermal conductivity Ks of the substrate. The rear heating-front detecting （RF） method is used to ensure the femtosecond temporal resolution. An intense laser beam is focused on the rear surface to heat the film, and another weak laser beam is focused on the very spot of the front surface to detect the change in the electron temperature. By varying the optical path delay between the two beams, a complete electron temperature profile can be scanned. Different from the normally used single-layer model, the double-layer model involving interfaciM thermal resistance is studied here. The electron temperature cooling profile can be affected by the electron energy transfer into the substrate or the electron-phonon interactions in the metallic films. For multiple-target optimization, the genetic algorithm （GA） is used to obtain both G and R. The experimental result gives a deep understanding of the mechanism of ultra-fast heat transfer in metals.